2021
DOI: 10.1097/pr9.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for pain chronicity in low back pain: a systematic review

Abstract: Supplemental Digital Content is Available in the Text. Several prognostic factors are related to low back pain chronicity, and these should be taken into account when planning more comprehensive models in its prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 138 publications
5
69
2
4
Order By: Relevance
“…This review has identified poor postural ergonomics, prolonged standing, prolonged sitting, whole body vibration, repetitive bending and twisting movements and lifting heavy objects as the most important biomechanical risk factors for CLBP. This result is in line with reviews from high income countries [ 56 , 57 , 58 ]. In order to mitigate the risk of CLBP due to occupational biomechanical stressors, proper workplace risk assessment by a qualified professional should be made mandatory and measures should be taken to ensure adherence to proper office ergonomic set-ups, no lifting policy, health education and promotion at workplace should be implemented.…”
Section: Discussionsupporting
confidence: 92%
“…This review has identified poor postural ergonomics, prolonged standing, prolonged sitting, whole body vibration, repetitive bending and twisting movements and lifting heavy objects as the most important biomechanical risk factors for CLBP. This result is in line with reviews from high income countries [ 56 , 57 , 58 ]. In order to mitigate the risk of CLBP due to occupational biomechanical stressors, proper workplace risk assessment by a qualified professional should be made mandatory and measures should be taken to ensure adherence to proper office ergonomic set-ups, no lifting policy, health education and promotion at workplace should be implemented.…”
Section: Discussionsupporting
confidence: 92%
“…regarding impact of pain on psychological and mood variables, especially anxiety, are consistent with data from other chronic pain conditions. 23,24 It might also be expected that USS severity would be related to sleep disturbance based on interruptions from nighttime frequency and urge, but the finding of USS-gp being most associated with increased sensory sensitivity and decreased physical well-being suggest a broader sensory-alteration phenotype may be underlying increased urinary frequency and urgency. PPS and USS both showed significant and independent associations with severity of nonpelvic pain, fatigue and depression but not number of nonpelvic pain locations.…”
Section: Discussionmentioning
confidence: 99%
“…With 32% of workers not back at work after 1 month, it has been suggested that interventions targeting individual-level risk factors should be implemented soon after injury to prevent long-term work absence [ 36 ]. The transition rate from acute to chronic LBP is significantly higher in obese adults, smokers, those with severe and very severe baseline disability and in adults diagnosed depression/anxiety, with biomechanical, psychological and psychosocial factors identified as prognostic factors for the development of chronic back pain [ 37 ]. In particular, depressive symptoms are a significant risk factor for the report of future back pain in older adults [ 38 ].…”
Section: Discussionmentioning
confidence: 99%